PENYUSUNAN PAKET PELATIHAN PENGEMBANGAN KECERDASAN INTRAPERSONAL UNTUK MAHASISWA - Rina Sukawati (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
The purpose of this research was to develop training package for intrapersonal intelligence development for the students of Educational Technology Department, School of Education, State University of Jakarta. The package was develop by employing Instructional Development Model. The research resulted in training package for intrapersonal intelligence development for the university students which is expected to be applicable or adjustable for trainings and the other universities for the similar purposes. A set of recommendation is given in using this package to be effective and efficient.